Telaah Fonologi dalam Pembelajaran Maharah Qiro'ah pada Anak Disleksia di RA Mamba’ul Hisan Surabaya: Phonology Study in Maharah Qira’ah Learning for Dyslexic Children at RA Mamba'ul Hisan Surabaya - Hasan, Laili Mas Ulliyah; Adhimah, Syifaul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Reading difficulties or dyslexia pose a big challenge for children, especially in understanding Arabic texts due to the language's unique morphophonemic rules. This study aims to understand how children with dyslexia face challenges in acquiring basic reading skills in Arabic and to identify effective teaching strategies to improve their Maharaj qira'ahQur'an This research method uses a qualitative approach, combining literature analysis, observation, and experimentation in the educational environment at RA Mamba'ulMamba'ulHisan Surabaya. A literature review was initially conducted to build a theoretical foundation, exploring previous studies on phonology, reading teaching, and qira'ah pedagogy. Data collection techniques through observation and experiments are carried out by applying teaching strategies identified from literature and observation analysis into classroom practice. The collected data was analyzed to evaluate the effectiveness of this strategy in increasing the maharah qira'ah of dyslexic children. Research findings show that phonological awareness is very important in learning maharah qira'ah and that phonology-based teaching strategies significantly improve reading and comprehension skills in dyslexic children. This research contributes to developing inclusive teaching practices, especially at RA Mamba'ulMamba'ulHisan Surabaya, providing valuable insight into effective educational strategies for children with reading difficulties.